Strategic pathways and regulatory choices for effective GHG reduction in hydrocarbon based economy: Case of Oman - Yassine Charabi; Talal Al-Awadhi; B.S. Choudri (Energy Reports, 2018)
The sultanate of Oman is a high-income country with economy dominated by hydrocarbon production accounting for 47.2% of GDP in 2014. Of the total, crude oil production contributed 43.8% to GDP while natural gas output accounted for contributed 3.4% of economic output. The sustained economic growth, urban sprawl and industrialization have maintained a continuous rising in energy demand. The consumption of oil and natural gas has doubled and tripled respectively, over the last decade. The diversification of the economy faces concerns about future energy security as conventional fossil fuel resources dwindle and its young population continues to grow rapidly. Oman faces the challenge of harmonizing its aspirations for rapid economic growth with a pressing need to address low-carbon, climate-resilient development. Internationally, Oman has voluntarily agreed to reduce GHG emissions 2% by 2030. The diversifications of the economy away from hydrocarbons requires an ambitious plan to diversify Oman’s energy mix while driving economic growth and technological innovation. Specifically, this paper focuses on providing an objective strategic pathways and regulatory choices that can serve as a starting point for policy makers when discussing how best to achieve GHG emission reductions in Oman. This study intentionally focus on the energy sector, the sector responsible for the largest share of GHG emissions in Oman. Keywords: Oman, Hydrocarbon economy, Pathways, GHG reduction, Climate change mitigation